2008
DOI: 10.1016/j.ymgme.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional multicenter study of patients with urea cycle disorders in the United States

Abstract: Inherited urea cycle disorders comprise eight disorders (UCD), each caused by a deficiency of one of the protein that is essential for ureagenesis. We report on a cross sectional investigation to determine clinical and laboratory characteristics of patients with UCD in the United States. The data used for the analysis was collected at the time of enrollment of individuals with inherited UCD into a longitudinal observation study. The study has been conducted by the Urea Cycle Disorders Consortium (UCDC) within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
176
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 196 publications
(187 citation statements)
references
References 11 publications
8
176
2
1
Order By: Relevance
“…Hyperammonemia-related neurological injuries range from lethal cerebral edema to mild or subclinical cognitive impairment, depending on the severity of the defect (Gropman et al 2008), with the most severely affected patients typically presenting early in life (Brusilow and Maestri 1996;Summar et al 2008;Tuchman et al 2008). Ornithine transcarbamylase (OTC) deficiency is the most common UCD, accounting for slightly more than half of all UCD cases (Summar et al 2008;Tuchman et al 2008;Batshaw et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperammonemia-related neurological injuries range from lethal cerebral edema to mild or subclinical cognitive impairment, depending on the severity of the defect (Gropman et al 2008), with the most severely affected patients typically presenting early in life (Brusilow and Maestri 1996;Summar et al 2008;Tuchman et al 2008). Ornithine transcarbamylase (OTC) deficiency is the most common UCD, accounting for slightly more than half of all UCD cases (Summar et al 2008;Tuchman et al 2008;Batshaw et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…4 Two recent studies determined that CTLN1 accounts for 14% to 27% of all reported UCDs. 15,16 Clinical symptoms of neonatal CTLN1 include delayed mental and physical development, irritability, recurrent vomiting, and lethargy. 9,17 Biochemically, CTLN1 is characterized by elevated plasma and urine concentrations of ammonia, citrulline, glutamine, and orotic acid, together with arginine deficiency.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] Even subjects with milder forms of ASA who are diagnosed early in life by newborn screens can develop neurocognitive deficiencies, attention deficit/hyperactivity disorder, developmental disability, and seizures despite early treatment intervention. [17][18][19] Supporting this notion, hepatic disease and hypertension have been reported in patients with ASA who have good metabolic control. 13,15,[20][21][22] These data suggest that the complex phenotype observed in ASA involves mechanisms beyond the blockade in ureagenesis and that ASA could serve as an example of a complex IEM in which disease phenotype extends beyond the loss of the enzymatic function of ASL.…”
mentioning
confidence: 78%